Fabrication of Flexible Microfluidic Strain Sensor by Laser Micromachining for Hand Motion Tracking - Khairul Fikri, Tamrin; Nurul Amirah, Khalid; Andrew Ragai, Henry Rigit (International Journal of Materials, Mechanics and Manufacturing, 2020)
Various types of strain sensors have been developed for providing reliable monitoring of human health. Microfluidic strain sensors is favourable for such an application due to its outstanding performance under a variety of three-dimensional deformations on the basis of elastic channel deformation. In this study, we report for the first time laser-machined micro-channels on fabricated epoxy substrate. Fabrication of flexible microfluidic sensor using soft clear epoxy is investigated. A ratio of 100:30 of epoxy resin-to-hardener results in a flexible and elastic epoxy layer. Laser micromachining (ablation) technique at varying parameters is conducted using Taguchi Experimental Design. Low number of passes for both kerf depth and kerf width gives an optimum response, while laser power and laser cutting speed differs for kerf width and kerf depth. Microstructure imaging is carried out using scanning electron microscopy for heat-affected zone examination.